AYAT-AYAT MODERASI BERAGAMA PERSPEKTIF TAFSIR IBNU KAS|I>R - Syaefudin Achmad (Tazkir: Jurnal Penelitian Ilmu-ilmu Sosial dan Keislaman, 2022)
Indonesia is a country that has six officially recognized religions. This plurality of course has the potensial to create horizontal conflictd between religious adherents. It is proven that in 2020 there have been many conflicts and cases of intolerance religious background, even in education. Religious moderation is an attitude that every citizen in Indonesia must have so that religious backround conflict do not occur. The purpose of his study was to examine the values of religious moderation in the verse of the al-Qur’an  perspective of Ibnu Kas|ir contained in the “PAI dan Budi Pekerti Class XII Book’. This study uses a qualitative approach, library research methods, documentation collections techniques, inductive analysis, and peer checking techniques for validity. Verses that contain religious moderation values in the book include Surah al-Baqarah verse 83, Surah Ali- Imran verse 159, Surah Ali Imran verses 190-191, and Surah Ma’idah verse 2.